TRADISI PENGAJIAN BEUT AL-QUR'AN SEBAGAI MODEL PEMBIASAAN IBADAH ANAK USIA DINI - Asnah Asnah; Kadim Bustami (lembaga Sepercenter, 2026)
Beut Al-Qur'an is a longstanding Acehnese communal tradition of Qur'anic recitation learning, historically conducted in the meunasah or at a teungku's (religious teacher's) house, typically after the Maghrib prayer until Isha. As a practice rooted in Aceh's identity as the 'Veranda of Mecca,' this tradition offers more than literacy in Qur'anic reading; it functions as an integrated model of worship habituation for children. This article aims to examine the historical and conceptual foundation of the Beut Al-Qur'an tradition, to describe its structure as a habituation-based model of worship education, and to analyze its contribution to early childhood religious character formation. This study uses a qualitative approach with a literature review (library research) method, collecting, analyzing, and synthesizing books, national and international journal articles, and historical documentation related to the Beut Al-Qur'an tradition, habituation theory, and early childhood religious and moral development. The results show that the structured and repetitive nature of Beut Al-Qur'an, encompassing Hijaiyah letter recognition, memorization, communal recitation, congregational prayer, and adab (etiquette) toward the teungku and fellow learners, aligns closely with behaviorist habituation principles and Islamic pedagogical concepts of habituation (ta'wid), making it an effective informal curriculum for instilling worship practices, discipline, and religious character in early childhood. The article concludes that the Beut Al-Qur'an tradition, when intentionally revitalized and thoughtfully integrated with Islamic early childhood education (PAUD Islam), offers a culturally authentic and pedagogically sound model for cultivating lifelong worship habits and religious character in children, while also preserving a valuable component of Aceh's Islamic educational heritage.